PCB (Printed Circuit Board) Etching Machine Using ESP32-Camera Based Internet Of Things - Adi Prasetyo; Jamaaluddin Jamaaluddin; Izza Anshory (Universitas Darul Ulum, 2023)
In general, today's technology is made automatically. Starting from car alarem, to automatic parking. This very rapid technological development makes humans create equipment that can minimize human activities.The etching process can also be called the Printed Circuit Board screen printing process, which is the creation of paths or layouts that will connect between electrical components. PCB Etching Machine is a tool used to dissolve metal parts that are not designed on a plain PCB board by using a mixture of chemical solutions, namely ferrite cloride. The manual PCB process usually takes a long time and has a risk of being exposed to ferric chloride solution for users. This article discusses how to make an automatic etching machine tool with a Microcontroller module that has a camera feature to monitor the results of editing on a copper board. With the time method as the key to perfect results during the checking process. For as a drive, namely using a Servo Motor. The microcontroller used on this machine is ESP32 Camera based on Internet of things Telegram as a Data Base media. For software design using fritzing software applications. The success of PCB etching machines in this study is seen from tool testing ranging from voltage testing, microcontroller testing, real time a clock testing and Internet Of Things system testing. Made a description of success, this etching machine can be used and said to be successful. In conclusion, a machine or tool made with the latest version if not researched, designed and tested it cannot be successful.